Evaluasi Tata Kelola Teknologi Informasi Aplikasi Layanan Di PT.PQR Dengan Cobit 4.1 - Wishnu Aribowo Probonegoro; Lili Indah Sari; Parlia Romadiana (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
PT PQR is a company engaged in the application of shipping services. It is important for PT PQR to manage and utilize information technology well, but there has never been an assessment of the management system and its application. The author conducted research to assess the management of information technology using the COBIT 4.1 standard, which has 34 processes. This research was conducted through observations, interviews, and measurement of maturity levels, with the aim that PT PQR knows the information technology governance that is carried out, and knows the gaps that exist so that they can be resolved immediately to improve services and compete with other companies. The results showed that the current maturity level at PT PQR is close to level 3, with 14 Information Technology processes in two domains, namely Delivery Support and Monitoring Evaluate. PT PQR has clear and written standard procedures regarding the procedures and management of information technology, which are socialized among management and employees. Overall, the maturity level evaluation shows that PT PQR has fairly good IT governance, with an average achievement close to the expected target. The DS domain has an almost optimal performance with an achievement of 99%, while the ME domain requires more attention to increase the achievement from 90% to 100%. Improvement efforts can be focused on areas that require improvement based on the findings of this analysis.